Does ‘Language’ Form Our ‘Thought’? - Rieko Matsuoka (East European Journal of Psycholinguistics, 2014)
As early as 1799, Humboldt initiated to wonder the gravity of ‘language’. Indeed, there exists much diversity in linguistic forms in human societies and, translation is necessary in order to share literary works, among different language users. During the process of translating culturally-colored discourse, some important features of a given society may well be revealed. As an empirical example, a script of rakugo, which is the traditional Japanese performance art of telling comic stories, is used as the data for analysis because rakugo can be regarded as a genre of natural, spoken Japanese discourse. In fact, Katz (as cited in Wardy, 2006) suggests that linguistic relativity threatens universal inter-translatability. In this study, focusing on zero personal pronouns, the notion of linguistic relativity is examined, related to the Japanese sense of self and the Japanese worldview that includes seken (life-world). This seems to reveal linguistic relativity (e.g., Humboldt 1999; Sapir 1921/2004) that different perspectives on reality often manifest themselves as specific features of language use in speech communities, as some empirical studies have been conducted, starting with Humboldt’s original research (1999) on the Kawi language.ReferencesAbe, Kinya. (2001). Academia and [seken] (Gakumon to [seken]: 学問と「世間」).Tokyo: Iwanami.Adler, G. J. (2009). Wilhelm Von Humboldt’s Linguistical Studies, BiblioBazaar.Bloomfield, L. (1922). Review of language. Classical Weekly, 15, 142-143.Boronditsky, L. (2001). Does language shape thought?: Mandarin and English speakers’conceptions of time. Cognitive Psychology, 43, 1-22.Chaudhary, N. (2003). Speaking the self into becoming? Culture & Psychology, 9(4), 471-486.Davies, I. R. L. (1998). A study of colour grouping in three languages: A test of thelinguistic relativity hypothesis. British Journal of Psychology, 89, 433-452.Hall, E. (1976). Beyond culture. Garden City, New York: Anchor Press.Handler, R. (1986). The aesthetics of Sapir’s language. In: New perspectives in language,culture, and personality, William Lowan, Michael. K. Foster, and E. F. K. Koerner, Eds.Amsterdam: John Benjamin.Humboldt, W. von. 1999. On Language: on the diversity of human languages constructionand its influence on the mental development of the human species. Cambridge University Press. January, D., Kako, E. (2007). Re-evaluating evidence for linguistic relativity: Reply toBoroditsky (2001). Cognition, 104, 417-426.Kuwayama, T. (1992). The reference other orientation. In: Japanese sense of self, NancyRosenberger, Ed. New York: Cambridge University Press, 121-151.Lebra, S. T. (2004). The Japanese self in cultural logic. Honolulu: University of Hawai’iPress.Lowie, R. H. (1923). Review of language. American Anthropologist,25: 90-93.Lucy, J. A. (1992). Language diversity and thought. Cambridge: Cambridge UniversityPress.Lucy, J. A. (1997). Linguistic relativity. Annual Review of Anthropology, 26: 291-312.Lucy, J. A. and Shweder, R. A. (1979). Whorf and his critics: linguistic and nonlinguisticinfluences on color memory. American Anthropologist, New Series, Vol. 81(3), 581-615.Ohta, A. S. (1991). «Evidenciality and politeness in Japanese.» Issues in applied linguistics2(2), 211-238.Ozgen, E., Davies, I. (2002). «Acquisition of categorical color perception: A perceptuallearning approach to the linguistic relativity hypothesis.» Journal of Experimental Psychology,131(4), 477-493.Pinker, S. (1995/2007). The language instinct: How the mind creates language. N.Y.:Harper Perennial.Sapir, E. (1921/2004). Language: An introduction to the study of speech. N.Y.: Harcourt,Bruce & Company.Sato, N. (2001/2007). Phenomenology of [seken] [Seken no genshoogaku(「世間」の現象学)]. Tokyo: Seikyusha.Slobin, D. I. (1996). From «thought and language» to «thinking and speaking.» In:Rethinking Linguistic Relativity, John. J. Gumperz, and Steven. C. Levinson, Eds. Cambridge:Cambridge University Press. 70-96.Slobin, D. I. (2003). Language and thought online: Cognitive consequences of linguisticrelativity.» In Language in mind: Advances in the study of language and thought, D. Gentner, andS. Goldin-Meadow, Eds. Cambridge, M.A.: MIT Press, 157-192.Spier, L, Hallowell, A., Newman, S. (1941). Language, culture, and personality: Essaysin memory of Edward Sapir. Menasha, Wis.: Sapir Memorial Publication Fund.Tatara, N., Yagihashi, H. (2007). The interface of cognition and language − Fromlinguistic relativity. [Ninchi to gengo no setten−Gengosoutaironwokangaeru] Journal of HumanLinguistics, 6, 10-14.Wardhaugh, R. (1986). An introduction to sociolinguistics. Malden, M.A.: Blackwell.Wardy, R. (2006). Aristotle in China: Language, categories and translation. London:Cambridge University Press.Wassmann, J., Dasen, P. (1998). Balinese spatial orientation: Some empirical evidence ofmoderate linguistic relativity. The Jounal of the Royal Anthropological Institute of Great Britainand Ireland, 4(4), 689-711.Watanabe, K. (2007). Discourse analysis of the first executive meeting for internationalmerging: from the perspective of indexicity in addressing forms. [Kokusai gappeikigyo nodaiikkaitorishimariyakukai no danwabunseki: Yobikakekeitai no shihyousei no shitenkara].Journal of Human Linguistics, 6, 15-18.30. Whorf, B. L. (1956). Language, thought, and reality. Cambridge, M.A.: MIT Press.